Mechanisms of Electrical Activation and Conduction in the Gastrointestinal System: Lessons from Cardiac Electrophysiology - Tse, Gary; Lai, Eric Tsz Him; Yeo, Jie Ming; Tse, Vivian; Wong, Sunny Hei (Frontiers in Physiology, 2016)
The gastrointestinal (GI) tract is an electrically excitable organ system containing multiple cell types, which coordinate electrical activity propagating through this tract. Disruption in its normal electrophysiology is observed in a number of GI motility disorders. However, this is not well characterized and the field of GI electrophysiology is much less developed compared to the cardiac field. The aim of this article is to use the established knowledge of cardiac electrophysiology to shed light on the mechanisms of electrical activation and propagation along the GI tract, and how abnormalities in these processes lead to motility disorders and suggest better treatment options based on this improved understanding. In the first part of the article, the ionic contributions to the generation of GI slow wave and the cardiac action potential (AP) are reviewed. Propagation of these electrical signals can be described by the core conductor theory in both systems. However, specifically for the GI tract, the following unique properties are observed: changes in slow wave frequency along its length, periods of quiescence, synchronization in short distances and desynchronization over long distances. These are best described by a coupled oscillator theory. Other differences include the diminished role of gap junctions in mediating this conduction in the GI tract compared to the heart. The electrophysiology of conditions such as gastroesophageal reflux disease and gastroparesis, and functional problems such as irritable bowel syndrome are discussed in detail, with reference to ion channel abnormalities and potential therapeutic targets. A deeper understanding of the molecular basis and physiological mechanisms underlying GI motility disorders will enable the development of better diagnostic and therapeutic tools and the advancement of this field.